Gap Analysis of Service Quality Level Using Servqual Method at Bank BRI Ciwastra Unit Bandung - Lestari, Linda; Sari, Oktora Yogi (Universitas Syiah Kuala, 2025)
Service quality is one of the key factors in determining customer satisfaction in banking. The phenomenon of customer complaints about the service at Bank BRI Unit Ciwastra Bandung highlights the need for an evaluation of the quality of services provided. This study aims to analyze the gap between customer expectations and perceptions of service quality using the SERVQUAL method. The research is quantitative and descriptive, with a sample size of 200 respondents selected through purposive sampling. Data were collected through a questionnaire based on the five SERVQUAL dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy, and were analyzed by calculating the gap between perceptions and expectations. The results show that all dimensions experienced a negative gap, with the reliability dimension showing the largest gap (-43.89%) and the empathy dimension showing the smallest gap (-44.19%). These findings indicate that the service at Bank BRI Unit Ciwastra does not fully meet customer expectations, particularly in terms of reliability and physical facilities. Therefore, it is recommended that Bank BRI Unit Ciwastra undertake comprehensive improvements, including enhancing facilities, training staff, and improving the service system to increase customer satisfaction and loyalty.